Upaya Pencegahan Perdarahan Pada Persalinan Ibu Hamil Dengan Anemia - Eka Safitri, Faradina; , Sulastri, S.Kp., M.Kes; , Faizah Betty R., A., S.Kep ., M.Kes (2017)
Background: Maternal death rate is still very high. Especially the case of bleeding in childbirth. Frequently found problems and which includes the cause of bleeding in the mother during childbirth is anemia or lack of blood. The causes of pregnant women who are anemic are blood loss, lack of red blood cell production or destruction of red blood cells faster than normal. It can also be caused by lack of iron supplements, vitamin C, vitamin B12 and folic acid and protein-containing foods, vitamins and minerals. If the Hb levels in pregnant women are less than 11 g / dl then it said to be anemia and treatment should be done as soon as possible. Objectives: The objectives of the nursing care to pregnant women clients with anemia are to prevent bleeding during labor. Methods: The method used is descriptive method of case studies that include assessment, intervention, implementation and evaluation of nursing. Results: After nursing care for 3 days the results obtained nursing problems resolved in part, then it require further treatment and cooperation of client and family which indispensable for the success of nursing care. So that the client's nursing problem about the risk of bleeding can be carried out properly and the problem can be resolved soon.